2007
DOI: 10.1074/jbc.m700641200
|View full text |Cite
|
Sign up to set email alerts
|

β-Dystroglycan as a Target for MMP-9, in Response to Enhanced Neuronal Activity

Abstract: Matrix metalloproteinase-9 has recently emerged as an important molecule in control of extracellular proteolysis in the synaptic plasticity. However, no synaptic targets for its enzymatic activity had been identified before. In this report, we show that ␤-dystroglycan comprises such a neuronal activity-driven target for matrix metalloproteinase-9. This notion is based on the following observations. (i) Recombinant, autoactivating matrix metalloproteinase-9 produces limited proteolytic cleavage of ␤-dystroglyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
191
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 42 publications
4
191
2
Order By: Relevance
“…However, its fairly low enzymatic efficiency under our conditions might indicate that this event is finely modulated by conformational changes of b-DG. The recent discovery of a b-DG processing carried out by MMP-9 in response to enhanced neuronal activity (23,24) would strengthen the hypothesis that MMP-9 cooperates with the DG complex in the signal transduction.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, its fairly low enzymatic efficiency under our conditions might indicate that this event is finely modulated by conformational changes of b-DG. The recent discovery of a b-DG processing carried out by MMP-9 in response to enhanced neuronal activity (23,24) would strengthen the hypothesis that MMP-9 cooperates with the DG complex in the signal transduction.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, b-DG has been proposed to be the first substrate digested by MMP-9 in response to enhanced neuronal activity, playing a role in synaptic plasticity, learning and memory (23,24). These data suggest that modulating the a-DG/b-DG interaction may have a precise functional role and that MMP-9 may be involved in this physiological process.…”
Section: Introductionmentioning
confidence: 88%
“…On the other hand, some of our findings are not consistent with previous reports. For instance, a prominent increase in MMP-9 mRNA levels was observed in rats 2 h after a single 50 mg/kg PTZ dose (Rylski et al, 2009), and MMP-9 activity increased as early as 5 min after bicuculline treatment in mouse cortical cultures (Michaluk et al, 2007). More detailed examination of temporal changes and species differences in MMP-9 expression after single and repeated PTZ injection may help explain these discrepant results.…”
Section: Discussionmentioning
confidence: 87%
“…Repeated PTZ treatment increased protein and mRNA levels of BDNF in the hippocampi of kindled mice as described below, whereas protein levels of other substrates for MMP, such as laminin (Gu et al, 2005), ␤-dystroglycan (Michaluk et al, 2007), and NCAM (Hübschmann et al, 2005), did not change (Table 1). In fully kindled …”
Section: Mmp-9 Contributed To Ptz-induced Development Of Kindled Seizurementioning
confidence: 99%
“…Generally, MMPs cleave a potentially large number of extracellular matrix proteins and other cell-surface or cell-adhesion molecules (Sternlicht and Werb 2001), many of which are expressed in hippocampus and are involved in synaptic plasticity and/or memory (Strekalova et al 2002;Dityatev and Schachner 2003). A recent study (Michaluk et al 2007) has identified ␤-dystroglycan (␤-dg) as an activity-dependent target of MMP-9 cleavage in cultured cortical neurons. ␤-dg is a transmembrane protein that links, via association with ␣-dystroglycan, proteins of the extracellular matrix with the actin cytoskeleton (Higginson and Winder 2005).…”
Section: Discussionmentioning
confidence: 99%